Bycatch Quotas, Risk Pools, and Cooperation in the Pacific Whiting Fishery - Holland, Daniel S.; Martin, Chris (Frontiers in Marine Science, 2019)
The US Pacific whiting fishery uses mid-water trawl gear to target Pacific whiting off the US West Coast. The fishery is subject to sector-specific bycatch caps for Chinook salmon and several rockfish species (widow rockfish, canary rockfish, darkblotched rockfish, Pacific Ocean Perch (POP)). Chinook bycatch can include fish from endangered populations and rockfish stocks were recovering from severe depletion though most are now rebuilt. Catch of these species is rare and uncertain, making it difficult for vessels to meet strict individual performance standards. Consequently the industry has developed risk pools in which bycatch quota for a group of vessels is pooled, but vessels are required to follow practices that minimize bycatch risk including temporal and spatial fishing restrictions. The risk pools also require vessels to share information about bycatch hotspots enabling a cooperative approach to avoid bycatch based on real-time information. In this article we discuss the formation and structure of these risk pools, the bycatch reduction strategies they apply, and outcomes in the fishery in terms of observed bycatch avoidance behavior and utilization of target species. The analysis demonstrates the ability of these fishers to keep bycatch within aggregate limits and keep individual vessels from being tied up due to quota overages.